Graduates' perception of career success and skill emphasis in accounting programme in Nigerian institutions: An exploratory study (Journal of Business Management and Accounting, 2012)
Although a great deal of studies on skills expected of accounting graduates have been conducted in industrially advanced countries, interest of researchers in developing economies is recent. Accordingly, this study explores measures of career success and the perceptions regarding the level of emphasis given to both technical and generic skills in Nigerian tertiary institutions from the perspective of accounting graduates. The study is motivated by concerns of scholars and call by the Institute of Chartered Accountants of Nigeria. Based on data obtained from 192 graduates, salary and frequency of promotion are perceived to be stronger measure of career success while technical skills; business, computing and ethical skills; interpersonal and problem solving skills as well as communication skills emerged as four components of skills taught and it was found that more emphasis was placed on technical skills at the cost of other skills. The findings from this study will have implications for accounting education in developing countries in general and Nigeria especially.